IMPLEMENTASI ONE CHANNEL SYSTEM (OCS) PADA MEMORANDUM OF UNDERSTANDING TENTANG PENETAPAN DAN PERLINDUNGAN PEKERJA MIGRAN SEKTOR DOMESTIK: DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL - NIM. A1011201109, JOSEF PARTOGI GULTOM (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Malaysia is one of the most attractive countries for Indonesian migrant workers. In this case, the governments of Indonesia and Malaysia have signed a Memorandum of Understanding (MoU) on